Expanded noninvasive prenatal testing for fetal aneuploidy and copy number variations and parental willingness for invasive diagnosis in a cohort of 18,516 cases - Yunsheng Ge; Jia Li; Jianlong Zhuang; Jian Zhang; Yanru Huang; Meihua Tan; Wei Li; Jiayan Chen; Yulin Zhou (BMC, 2021)
Abstract Background Noninvasive prenatal testing (NIPT) has been wildly used to screen for common aneuplodies. In recent years, the test has been expanded to detect rare autosomal aneuploidies (RATs) and copy number variations (CNVs). This study was performed to investigate the performance of expanded noninvasive prenatal testing (expanded NIPT) in screening for common trisomies, sex chromosomal aneuploidies (SCAs), rare autosomal aneuploidies (RATs), and copy number variations (CNVs) and parental willingness for invasive prenatal diagnosis in a Chinese prenatal diagnosis center. Methods A total of 24,702 pregnant women were retrospectively analyzed at the Women and Children's Hospital from January 2013 to April 2019, among which expanded NIPT had been successfully conducted in 24,702 pregnant women. The high-risk expanded NIPT results were validated by karyotype analysis and chromosomal microarray analysis. All the tested pregnant women were followed up for pregnancy outcomes. Results Of the 24,702 cases, successful follow-up was conducted in 98.77% (401/446) of cases with common trisomies and SCAs, 91.95% (80/87) of RAT and CNV cases, and 76.25% (18,429/24,169) of cases with low-risk screening results. The sensitivity of expanded NIPT was 100% (95% confidence interval[CI], 97.38-100%), 96.67%(95%CI, 82.78-99.92%), and 100%(95%CI, 66.37-100.00%), and the specificity was 99.92%(95%CI, 99.87-99.96%), 99.96%(95%CI, 99.91-99.98%), and 99.88% (95%CI, 99.82-99.93%) for the detection of trisomies 21, 18, and 13, respectively. Expanded NIPT detected 45,X, 47,XXX, 47,XXY, XYY syndrome, RATs, and CNVs with positive predictive values of 25.49%, 75%, 94.12%, 76.19%, 6.45%, and 50%, respectively. The women carrying fetuses with Trisomy 21/Trisomy 18/Trisomy 13 underwent invasive prenatal diagnosis and terminated their pregnancies at higher rates than those at high risk for SCAs, RATs, and CNVs. Conclusions Our study demonstrates that the expanded NIPT detects fetal trisomies 21, 18, and 13 with high sensitivity and specificity. The accuracy of detecting SCAs, RATs, and CNVs is still relatively poor and needs to be improved. With a high-risk expanded NIPT result, the women at high risk for common trisomies are more likely to undergo invasive prenatal diagnosis procedures and terminate their pregnancies than those with unusual chromosome abnormalities.